Intensive Care Management of Non-Ischemic Dilated Cardiomyopathy with Morbid Obesity in a Parturient Undergoing Cesarean Section - Darmoko, Aris; Kestriani , Nurita Dian (Journal of Society Medicine, 2025)
Introduction: Dilated cardiomyopathy (DCM) in pregnancy is a rare but life-threatening condition, with reported incidence ranging from 1:4,950 deliveries in Europe to 2.38:1,000 deliveries in Asia. When complicated by morbid obesity, it significantly increases perioperative and critical care challenges, requiring a coordinated multidisciplinary approach to optimize maternal outcomes. Case Description: A 32-year-old primigravida with morbid obesity (BMI 49.5 kg/m²) and non-ischemic dilated cardiomyopathy presented with decompensated heart failure at 29 weeks of gestation. She underwent elective cesarean section under general anesthesia followed by 19 days of intensive care. Management included hemodynamic optimization with dobutamine infusion, restrictive fluid strategy targeting negative balance, stepwise ventilator weaning from mechanical ventilation to nasal cannula, and treatment of complications including electrolyte disturbances and postoperative delirium secondary to obesity hypoventilation syndrome (Pickwickian syndrome). Continuous hemodynamic monitoring using MostCare and invasive arterial pressure enabled precise titration of therapy. Conclusion: Successful maternal outcome in pregnant patients with dilated cardiomyopathy and morbid obesity can be achieved through comprehensive preoperative optimization, carefully selected anesthetic technique, and prolonged multidisciplinary intensive care. This case highlights the importance of integrated hemodynamic, respiratory, and metabolic management in this high-risk population.